HIV Testing, Behavior Change, and the Transition to Adulthood in Malawi - Beegle, Kathleen; Poulin, Michelle; Shapira, Gil (World Bank, Washington, DC, 2014)
For young adults living in countries with AIDS epidemics, getting an HIV test may influence near-term decisions, such as when to leave school, when to marry, and when to have a first child. These behaviors, which define the transition from adolescence to adulthood, have long-term implications on well-being and directly affect a person's risk of contracting HIV. Using an experimental design embedded in a panel survey from Malawi, this study assesses the impact of voluntary counseling and testing of young adults for HIV on these decisions. The results show negligible intent-to-treat effect of HIV testing on behaviors. There is some suggestive evidence on differential response by wealth and by prior beliefs about one's status.